Diversity, structure, and distribution of bacterioplankton and diazotroph communities in the Bay of Bengal during the winter monsoon - Wu, Chao; Narale, Dhiraj Dhondiram; Cui, Zhengguo; Wang, Xingzhou; Liu, Haijiao; Xu, Wenzhe; Zhang, Guicheng; Sun, Jun (Frontiers in Microbiology, 2022)
The Bay of Bengal (BoB) is conventionally believed to be a low productive, oligotrophic marine ecosystem, where the diazotroph communities think to play a vital role in adding “new” nitrogen through nitrogen fixation process. However, the diazotroph communities in the oceanic region of the BoB is still poorly understood though it represents most of the seawater volume. The present study investigated detailed account of the bacterioplankton community structure and distribution in the oceanic BoB during the winter monsoon using high throughput sequencing targeting the 16S rRNA and nifH genes. Our study observed diverse groups of bacterioplankton communities in the BoB including both cyanobacterial and non-cyanobacterial phylotypes. Cyanobacteria (Prochlorococcus spp. and Synechococcus spp.) and Proteobacteria (mainly α-, γ-, and 𝛿-Proteobacteria) were the most abundant groups within the bacterial communities, possessing differential vertical distribution pattern. Cyanobacteria were more abundant in the surface waters, whereas Proteobacteria dominated the deeper layers (75m). However, within the diazotroph communities, Proteobacteria (mainly γ-Proteobacteria) were the most dominant groups than Cyanobacteria. Function prediction based on PICRUSt revealed that nitrogen fixation was active to add fixed nitrogen in the surface waters, while nitrogen removal pathways (denitrification and anammox) stronger in deeper layers. Canonical correspondence analysis (CCA) indicated that temperature, salinity, and silicate were major environmental factors driving the distribution of the bacterial communities. Additionally, phosphate was also an important factor for regulating the diazotroph communities in the surface water. Overall, this study provides detailed information on bacterial communities and their vital role in the nitrogen cycles in the oligotrophic ecosystems.